Electrochemical performance of unsintered Ba0.5Sr0.5Co0.8Fe0.2O3-δ, La0.6Sr0.4Co0.8Fe0.2O3-δ, and La0.8Sr0.2MnO3-δcathodes for metal-supported solid oxide fuel cells - Yu Mi Kim (2018)
The electrochemical performances of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF), La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3-δ (LSCF), and La 0.8 Sr 0.2 MnO 3-δ (LSM) cathodes fabricated without pre-sintering were studied. The BSCF starting powder prepared by the glycine nitrate method exhibited a single perovskite structure and no secondary phase was detected using XRD. SEM images revealed that the unsintered BSCF particles were highly agglomerated even before exposure to the operating temperature of the solid oxide fuel cell (SOFC). Unlike the LSM and LSCF cathodes, the BSCF cathode could be sintered at the SOFC operating temperature of 1073 K, and therefore exhibited porosity and good connectivity among particles. As determined using electrochemical impedance spectroscopy measurements, the lowest polarization resistances were found to be 0.13 cm 2 for unsintered BSCF, 0.22 cm 2 for unsintered LSCF, and 3.19 cm 2 for unsintered LSM. The single-cell power density curves had maximal power densities of 0.91 W cm -2 , 0.77 W cm -2 , 0.60 W cm -2 for anode-supported SOFCs using unsintered BSCF, LSCF, and LSM cathodes, respectively. For practical aspect, the power densities of 0.72, 0.6 and 0.5 W cm -2 were obtained at 0.7 V from anode-supported SOFCs with unsintered BSCF, LSCF and LSM cathodes, respectively. The metal-supported cells ha ving unsintered BSCF cathode had maximum power densities at 0.82 W cm -2 , and a power density of 0.74 W cm -2 at 0.7 V was observed. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.